Study of clay soil properties when using the method of concentrated lime exposure - E. N. Alkaev; A. A. Lunev; V. V. Golubenko (Вестник СибАДИ, 2022)
Introduction. In the Siberian Federal Area, the abundance of clay soils sources with above-optimal moisture content significantly complicates the technology of operations, reduces the speed of work, and makes some reserves unusable. To solve these problems, the use of quicklime in preparation for quarrying of clay soils with above-optimal moisture content was considered.The experimental studies have been carried out on the dynamics of soil drainage (lightweight dust loam) from drilling a well filled with lightweight lime (concentrated lime method). During this study, three experiments were carried out on soil masses with different initial humidity, two of which were carried out under the influence of lime and one (control) without the effect thereof.In addition, the change in optimum humidity and maximum density of dry soil during lime injection into loamy soil (dosage from 2% to 6% by mass) was evaluated. On the basis of the results obtained and the analysis of literature sources rational distances between slots (wells) are justified when using concentrated lime action technology to drain soils with increased humidity in quarries.Negotiations and conclusions. On the basis of the results obtained in the course of the study, it can be concluded that drying the soil with lime by the proposed concentrated method has a positive effect on the physical and mechanical characteristics of the soil.